Auditory, visual and tactile hallucinations in a 16-year-old adolescent with high-dose duloxetine at one time - Cosgun, Sefa (Journal of Surgery and Medicine, 2020)
Duloxetine is a dual-acting serotonin-noradrenaline reuptake inhibitor. It has FDA approval for the diagnosis of Major Depressive Disorder (MDD), Generalized Anxiety Disorder (GAD), Diabetic Neuropathic Pain, Fibromyalgia, Chronic Skeletal Muscle Pain in adults, and GAD in children and adolescents. This article presents a 16-year-old female patient referred to the emergency department with hallucinations starting after she took a total of 330 mg/day duloxetine for headaches. It is thought that her experienced hallucinations may be due to increased dopamine, as a result of inhibition of serotonergic system and noradrenaline transport system. It is thought that this article will contribute to the literature in terms of pharmacokinetic and pharmacodynamic effects of duloxetine in children and adolescents.